Preemptive use of anti-inflammatories and analgesics in oral surgery: a review of systematic reviews - Pimenta, Régis Penha; Takahashi, Cristiane Midori; Barberato-Filho, Silvio; McClung, Delaine Cristina Ferreira; Moraes, Fabio da Silva; de Souza, Isabela Muniz; Bergamaschi, Cristiane de Cássia (Frontiers in Pharmacology, 2024)
Objectives. This review of systematic reviews evaluated the effectiveness and safety of the preemptive use of anti-inflammatory and analgesic drugs in the management of postoperative pain, edema and trismus in oral surgery. Material and methods. The databases searched were the Cochrane Library, MEDLINE, EMBASE, Epistemonikos, Scopus, Web of Science and Virtual Health Library, up to March, 2023. Pairs of reviewers independently selected the studies, extracted the data and rated their methodological quality using the AMSTAR-2 tool. Results. All of the 19 studies reviewed had at least two critical methodological flaws. Third molar surgery was the most common procedure (n=15) and the oral route the most frequent approach (n=14). The use of betamethasone (10mg, 20mg and 60mg), dexamethasone (4mg and 8mg), methylprednisolone (16mg, 20mg, 40mg, 60mg, 80mg and 125mg), prednisolone (10mg and 20mg) by different routes; and likewise of celecoxib (200mg), diclofenac (25mg, 30mg, 50mg, 75mg and 100mg), etoricoxib (120mg), ibuprofen (400mg and 600mg), ketorolac (30mg), meloxicam (7.5mg, 10mg and 15mg), nimesulide (100mg) and rofecoxib (50mg) administered by oral, intramuscular and intravenous routes were found to reduce pain, edema and trismus in patients undergoing third molar surgery. Data on adverse effects were poorly reported. Conclusion. Further randomized clinical trials should be conducted to confirm these findings, given the wide variety of drugs, doses and routes of administration used.